Considering ergonomics in the accident and emergency department: possible or not - Ahmad Rasdan Ismail; Shaik Farid Abdull Wahab; Rohayu Othman (2018)
Accident and Emergency Department is one of the medical treatment departments that deal with emergency medicine, where patients come without making any appointment in advance. In Malaysia, it was known as Casualty Department previously. The nature of Accident and Emergency Department is complex due to the unpredictability of this department, Accident and Emergency Department is a workplace for multiple types of individuals. This study looked into the numbers of studies that has been carried out in area of ergonomics at Emergency Department of Malaysia Hospitals compared to other department. Numbers of studies are compared to see the loop that exists in Accident and Emergency Department when it comes to ergonomics. This paper will see the ergonomics issues face by healthcare personnel compares to other department in hospitals. Findings showed that, Accident and Emergency Department of Malaysia Hospitals has not been given enough attention regarding the implementation or ergonomics.